EXTRACTION AND SPECTROPHOTOMETRIC DETERMINATION OF TANTALUM (V) WITH 2-HYDROXYTHIOPHENOL AND ITS DERIVATIVES IN THE PRESENCE OF HYDROPHOBIC AMINES - Zalov, Ali Z.; Verdizadeh, Naila A.; Aliyev, Sultan G.; Mammadova, Shafa A. (IJRDO-Journal of Applied Science, 2016)
Mixed-ligand complexes of Tantalum (V) with thiocatecholic compounds (TCs){2-hydroxythiophenol(HTP), 2,4-dihydroxythiophenol (DHTP), 2-hydroxy-5-chlorothiophenol (HCTP), 2-hydroxy-5-bromothiophenol (HBTP) and 2-hydroxy-5-iodothiophenol (HITP)} in the presence ofhydrophobic amines (Am) have been studied by spectrophotometry. As hydrophobic amine wereused aniline (An), N-methylaniline (MAn), N, N-dimethylaniline (DAn), aminopyridine (APy),dipyridyl (DiPy), guanidine (Gu), diphenylguanidine (DPG), and triphenylguanidine (TPG).Extraction of mixed ligand complexes is maximal at pH 2.4-6.8. The best organic solvent waschloroform. Under the optimum conditions, the molar absorptivities (emax) and the degrees ofTantalum extraction (R%) in this solvent were in the ranges (1.60-3.94)×104 L mol-1cm-1and(98.1-98.6)%, respectively. The molar ratio of the reacting species was 1:2:2 (Ta:TCs:Am). IfAPy and DiPy molar ratio is 1: 2: 1. The Beer’s law was applicable in the range of 1.0-100 µg· ml1. The method is free from common interferences. A procedure has been developed for extraction –spectrophotometric determination tantalum in steel.